Synthesis, characterization and C-H amination reactivity of nickel iminyl complexes - Dong, Yuyang; Lukens, James T; Clarke, Ryan M; Zheng, Shao-Liang; Lancaster, Kyle M; Betley, Theodore A (Chemical science (Cambridge), 2020)
Metalation of the deprotonated dipyrrin ( AdF L)Li with NiCl 2 (py) 2 afforded the divalent Ni product ( AdF L)NiCl(py) 2 ( 1 ) ( AdF L: 1,9-di(1-adamantyl)-5-perfluorophenyldipyrrin; py: pyridine). To generate a reactive synthon on which to explore oxidative group transfer, we used potassium graphite to reduce 1 , affording the monovalent Ni synthon ( AdF L)Ni(py) ( 2 ) and concomitant production of a stoichiometric equivalent of KCl and pyridine. Slow addition of mesityl- or 1-adamantylazide in benzene to 2 afforded the oxidized Ni complexes ( AdF L)Ni(NMes) ( 3 ) and ( AdF L)Ni(NAd) ( 4 ), respectively. Both 3 and 4 were characterized by multinuclear NMR, EPR, magnetometry, single-crystal X-ray crystallography, theoretical calculations, and X-ray absorption spectroscopies to provide a detailed electronic structure picture of the nitrenoid adducts. X-ray absorption near edge spectroscopy (XANES) on the Ni reveals higher energy Ni 1s → 3d transitions ( 3 : 8333.2 eV; 4 : 8333.4 eV) than Ni I or unambiguous Ni II analogues. N K-edge X-ray absorption spectroscopy performed on 3 and 4 reveals a common low-energy absorption present only for 3 and 4 (395.4 eV) that was assigned via TDDFT as an N 1s promotion into a predominantly N-localized, singly occupied orbital, akin to metal-supported iminyl complexes reported for iron. On the continuum of imido ( i.e. , NR 2− ) to iminyl ( i.e. , 2 NR − ) formulations, the complexes are best described as Ni II -bound iminyl species given the N K-edge and TDDFT results. Given the open-shell configuration ( S = 1/2) of the iminyl adducts, we then examined their propensity to undergo nitrenoid-group transfer to organic substrates. The adamantyl complex 4 readily consumes 1,4-cyclohexadiene (CHD) via H-atom abstraction to afford the amide ( AdF L)Ni(NHAd) ( 5 ), whereas no reaction was observed upon treatment of the mesityl variant 3 with excess amount of CHD over 3 hours. Toluene can be functionalized by 4 at room temperature, exclusively affording the N -1-adamantyl-benzylidene ( 6 ). Slow addition of the organoazide substrate (4-azidobutyl)benzene ( 7 ) with 2 exclusively forms 4-phenylbutanenitrile ( 8 ) as opposed to an intramolecular cyclized pyrrolidine, resulting from facile β-H elimination outcompeting H-atom abstraction from the benzylic position, followed by rapid H 2 -elimination from the intermediate Ni hydride ketimide intermediate. Nickel-supported nitrenoids exhibit iminyl character, as determined by multi-edge XAS and TDDFT analysis, demonstrate efficacy for C-H activation and nitrene transfer chemistry.